2012
DOI: 10.1186/cc10537
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review: Sepsis and septic shock - the potential of gene arrays

Abstract: Over the past decade several investigators have applied microarray technology and related bioinformatic approaches to clinical sepsis and septic shock, thus allowing for an assessment of how, or if, this branch of genomic medicine has meaningfully impacted the field of sepsis research. The ability to simultaneously and efficiently measure the steady-state mRNA abundance of thousands of transcripts from a given tissue source (that is, 'transcriptomics') has provided an unprecedented opportunity to gain a broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 73 publications
(113 reference statements)
1
46
0
1
Order By: Relevance
“…This common response included typical proinflammatory, anti-inflammatory, metabolic, and T-cell signaling pathways, which is in accordance with previous studies. 26,46 Pathways with reduced expression in patients with ,50 3 10 9 /L platelets relative to patients with normal platelet counts predominantly involved leukocyte adhesion, extravasation, and diapedesis. In this respect, it should be noted that the axonal guidance signaling pathway largely entails genes involved in cytoskeletal reorganization (for example, TUBA8, TUBB, and PXN), while Ephrin receptor signaling is important for leukocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…This common response included typical proinflammatory, anti-inflammatory, metabolic, and T-cell signaling pathways, which is in accordance with previous studies. 26,46 Pathways with reduced expression in patients with ,50 3 10 9 /L platelets relative to patients with normal platelet counts predominantly involved leukocyte adhesion, extravasation, and diapedesis. In this respect, it should be noted that the axonal guidance signaling pathway largely entails genes involved in cytoskeletal reorganization (for example, TUBA8, TUBB, and PXN), while Ephrin receptor signaling is important for leukocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray data and genome-wide expression profiling also have been increasingly applied to identify novel pathways and therapeutic gene targets, sepsis-related biomarkers [6,[15][16][17]. A microarray-based study in children with septic shock demonstrated that development age is a major contributor to sepsis heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Several obvious virtues of the integrative PIN-mRNA expression approach are that (1) it resolves some of the inherent problems involved with analyzing gene expression data separately, such as poor signal to noise ratios and the nodes of explaining gene expression features, (2) integrative PIN-mRNA expression studies have indeed helped tease out relevant patterns of expression variation in the contextual framework of signaling pathways and protein complexes, (3) combination of PINs and expression correlation networks could distinguish direct and indirect correlations, further remove the (long-distance) indirect correlation between genes [14]. PINs have been applied to explore the disease associated genes and pathways in many literature [15]. Disrupted pathways in glioblastoma multiforma have been identified by tracking back paths through the human PINs from differentially expressed gene (target).…”
Section: Introductionmentioning
confidence: 99%
“…They are the most common targets of measurement when microarrays and RNA-seq are utilised, by way of cDNA libraries, and provide a picture of gene expression. While they do take into account transcriptional regulatory mechanisms, they are limited in only providing a pointin-time snapshot of genetic expression and furthermore do not give information on post-translational modification and regulation (Wong, 2012).…”
Section: Transcriptomicsmentioning
confidence: 99%